KONFLIK BATIN TOKOH WANITA DALAM NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY - Ningrum, Cahya Hardianti; Asri, Yasnur; Marni, Silvia (Pendidikan Bahasa Indonesia, 2013)
This study is qualitative research by using descriptive methods. Data of this research is intrinsic element that support inner figure conflict in novel âCinta Suci Zahranaâ. Source of the data is novel âCinta Suci Zahranaâ created by Habiburrahman El Shirazy publish in 2011 that cansists of 284 page divide in 18 chapters. The purpose of this research is to describe inner conflice woman based on âIdâ, âEgoâ, and âSuper Egoâ that is caused of inner conflict in novel âCinta Suci Zahranaâ created by Habiburrahman El Shirazy. This research explains that Zahrana. Who has the woman figure in this novel have inner conflict because of âEgoâ affected of herself. She too keep the ego was in hersef, so that she was wrong in taking decisions. She was sad because cold treatment of her parents when she succeed made an achievement that is proud. It causes of âId aspectâ that affected herself. Then, inner conflict Zahrana more added when she proposed bya Mr. Sukarman, the people who has bad attitude and as Dekan at the university where she was teach at that place. She decided to resign as a lecturer at Univ. Magunkarsa because she didnât receive Mr. Surkarmanâs propose. She chooses that decision because of âSuper Egoâ aspect an herselt. When her fiance was died, âId aspectâ always affect herself. Noeverhteless she was able to resolve the problem. Finally, Zahrana find her soulmate, she was married with Hasan, who has her students, and she lived happily.